Milestones in Natural Lubrication of Synovial Joints - Ruggiero, Alessandro (Frontiers in Mechanical Engineering, 2020)
From years, the possibility to model, from the physical and mathematical point of view, the tribological phenomena acting in human natural synovial joints has been constituting a great challenge for researchers and scientists. This short review is aimed to summarize main findings on the lubrication modelling in human synovial joints through the years, starting from first insights, underlining the evolution of the proposed theories. The complexity of the natural human synovial joints, in which, biological, fluid dynamic, and tribological phenomena take place, makes this research area fascinating for scientists coming from several investigation fields. This manuscript underlines how, nowadays, on the basis of the findings achieved by scientists thorough the years, it is necessary a deep scientific cooperation between researchers from the different branches of the involved disciplines to achieve a greater knowledge about these tribo-systems taking in to account more points of view.